Mycobacterial infections in horses: a review of the literature - I. Pavlik; P. Jahn; L. Dvorska; M. Bartos; L. Novotny; R. Halouzka (Veterinární Medicína, 2004)
Mycobacterial infections are rarely diagnosed in horses. Nevertheless, it was possible to obtain noteworthy information on diagnosis, manifold clinical signs and epidemiological relationships from available literature. It has been more than 60 years since a review dealing with this topic was published. Based on literature analysis, it was found that after bovine tuberculosis control in cattle and other animals in Central Europe, Mycobacterium avium complex (MAC) members were the most commonly found causal agents of mycobacterial infections in horses. At present, mycobacterial infections caused both by M. tuberculosis complex and MAC are occasionally diagnosed in horses inCentral Europe. Finally, under certain conditions, horses may become a source of mycobacterial infections for other animal species or for immunocompromised humans